Water deficit induces changes in H⁺-ATPase activity and its gene expres sion in Zea mays L. roots - Ovrutska, I.I.; Bluma, D.A. (Доповіді НАН України, 2016)
We investigated the functioning and the gene expression of H⁺-ATPase in the microsomal fraction enri ched with plasmalemma vesicles isolated from roots of two Zea mays cultivars: Dostatok (drought resistant) and Pereyaslivskiy (moderately tolerant to drought). Both cultivars grew during 21 days under the optimal water supply (soil moisture — 70 %, control) and during 10 days under the water deficit conditions (soil moisture — 30 %, experiment). An increase in the H⁺-ATPase hydrolytic activity in both cultivars under the water stress has been detected under drought. The enzyme hydrolytic activity is increased by twice in Dostatok and by1.3 times in Pereyaslivskiy. The H⁺-ATPase gene expression levels in both cultivars also increased under water deficit. It is shown that, in roots of both maize cultivars, the increase of four isoforms of H⁺-ATPase gene expression correlates with the increase of the hydrolytic enzyme activity under water stress conditions. However, these parameters are more sustainable in the drought-resistant cultivar Dosta tok, by allowing one value to use the hydrolytic activity of H⁺-ATPase as a biomarker of drought resistance for corn varieties.